Integrating Artificial Intelligence In Language Acquisition: A Comparative Study Of Adaptive Learning Platforms In Indonesian Efl Classrooms - Aisyah Aulia Putri; Nurasia Natsir (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This study investigates the implementation and effectiveness of artificial intelligence-driven adaptive learning platforms in English as a Foreign Language (EFL) classrooms across urban and rural Indonesian educational settings. Through a mixed-methods approach involving 247 students and 12 teachers from eight institutions, this research comparatively analyzes three prominent AI language learning platforms: LinguaLearn AI, AdaptEd English, and AI Tutor Pro. The findings reveal significant differences in learning outcomes, with AI-enhanced platforms demonstrating a 27% improvement in language proficiency compared to traditional methods. However, implementation challenges including digital literacy barriers, internet connectivity issues, and cultural adaptation requirements were identified, particularly in rural contexts. The study proposes a contextually responsive framework for integrating AI language learning technologies in developing EFL environments, contributing to the growing discourse on educational technology in linguistically diverse settings. This research highlights the potential of AI to personalize language acquisition while emphasizing the necessity of culturally and infrastructurally appropriate implementation strategies.